Perencanaan Rute dan Kecepatan AGV pada Sistem Pergudangan Menggunakan Algoritma Ant Colony Optimization - Desi; Renilalili; Arpan Efendi (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2019)
The problem in this study is how to improve the quality of customer service CV. Sinar Jaya Agung with servqual method and quality function deployment with the aim to find out consumer perceptions with the servqual method, to determine the servqual gap value between consumer perceptions and expectations, and to improve service quality according to the needs and desires of consumers by using the quality function deployment method. The results of this study indicate that the higher the value of customer satisfaction performance, the higher the level of consumer perceptions of attributes by respondents, the value of servqual gap obtained the highest value of 0.35 on the attributes of employees having competence and professional in serving customers. Thus it can be interpreted that the quality of customer service provided can be said to be good. The results of testing the quality function deployment show that to improve service quality according to the needs and desires of consumers, the company must make several improvements, including: the location of the company must be easily accessible to consumers, provision of cleaning checklists, routine training to employees, and good service from employees to consumers.